Pengaruh Promosi terhadap Perilaku Pembelian Produk Tata Rias Wajah (Make Over) pada Mahasiswa Tata Rias dan Kecantikan - T, Miftahur Rahmi Anasti; Putri, Nadila Dwi; Dewi, Siska Miga (Al-DYAS, 2025)
This study aims to reveal the effect of promotion on purchasing behavior of Make Over brand makeup products among students of the Department of Cosmetology and Beauty at Padang State University. The research method uses a quantitative descriptive approach with a correlational design. Data were collected through a Likert Scale-based questionnaire distributed online, with a proportional sampling technique. Validity and reliability tests were conducted using SPSS, followed by product moment correlation analysis to test the relationship between variables. The results showed that the promotion carried out by the Make Over company had an average score of 73.17%, while the purchasing behavior of students had an average score of 69.18%, both of which were in the moderate category. Correlation analysis shows a significant relationship between promotion and purchasing behavior with a correlation value of r = 0.602. Hypothesis testing confirms that promotion has a significant effect on purchasing behavior (t count = 8.617> t table = 2.000). This study confirms the importance of the right promotional strategy in influencing consumer behavior, as well as the need for students to consider rational factors in purchasing cosmetic products to maximize their use.